Eradicating uropathogenic Escherichia coli biofilms with a ciprofloxacin–dinitroxide conjugate. Issue 5 (8th March 2019) - Verderosa, Anthony D.; Harris, Jessica; Dhouib, Rabeb; Totsika, Makrina; Fairfull-Smith, Kathryn E.
Abstract : Biofilm-related UTIs are problematic infectious diseases worldwide; here we have developed a novel ciprofloxacin–dinitroxide conjugate with potent UPEC biofilm-eradication activity. Abstract : Urinary tract infections (UTIs) are amongst the most common and prevalent infectious diseases worldwide, with uropathogenic Escherichia coli (UPEC) reported as the main causative pathogen. Fluoroquinolone antibiotics are commonly used to treat UTIs but for infections involving UPEC biofilms, which are commonly associated with catheter use and recurrent episodes, ciprofloxacin is often ineffective. Here we report the development of a ciprofloxacin–dinitroxide (CDN) conjugate with potent UPEC biofilm-eradication activity. CDN11 exhibited a 2-fold increase in potency over the parent antibiotic ciprofloxacin against UPEC biofilms. Moreover, CDN11 resulted in almost complete UPEC biofilm cell eradication (99.7%) at concentrations as low as 12.5 μM, and significantly potentiated ciprofloxacin's biofilm-eradication activity against UPEC upon co-administration. The biofilm-eradication activity of CDN11 highlights the potential of nitroxide functionalized antibiotics as a promising strategy for the treatment of biofilm-related UTIs.